The Use of Cubic Splines in the Numerical Solution of Fractional Differential Equations - W. K. Zahra; S. M. Elkholy (International Journal of Mathematics and Mathematical Sciences)
Fractional calculus became a vital tool in describing many phenomena appeared in physics, chemistry as well as engineering fields. Analytical solution of many applications, where the fractional differential equations appear, cannot be established. Therefore, cubic polynomial spline-function-based method combined with shooting method is considered to find approximate solution for a class of fractional boundary value problems (FBVPs). Convergence analysis of the method is considered. Some illustrative examples are presented.